Saliva microRNA signature to diagnose endometriosis: A cost‐effectiveness evaluation of the Endotest®. (19th December 2022) - Ferrier, Clement; Bendifallah, Sofiane; Suisse, Stéphane; Dabi, Yohann; Touboul, Cyril; Puchar, Anne; Zarca, Kevin; Durand Zaleski, Isabelle
Abstract: Objective: To evaluate a saliva diagnostic test (Endotest®) for endometriosis compared with the conventional algorithm. Design: A cost‐effectiveness analysis with a decision‐tree model based on literature data. Setting: France. Population: Women with chronic pelvic pain. Methods: Strategy I is the French algorithm, representing the comparator. For strategy II, all patients have an Endotest®. For strategy III, patients undergo ultrasonography to detect endometrioma and patients with no endometrioma detected have an Endotest®. For strategy IV, patients with no endometrioma detected on ultrasonography undergo pelvic magnetic resonance imaging (MRI) to detect endometrioma and/or deep endometriosis. An Endotest® is then performed for patients with a negative result on MRI. Main outcomes measures: Costs and accuracy rates and incremental cost‐effectiveness ratios (ICERs). Three analyses were performed with an Endotest® priced at €500, €750, and €1000. Probabilistic sensitivity analysis was conducted with Monte Carlo simulations. Results: With an Endotest® priced at €750, the cost per correctly diagnosed case was €1542, €990, €919 and €1000, respectively, for strategies I, II, III and IV. Strategy I was dominated by all other strategies. Strategies IV, III and II were, respectively, preferred for a willingness‐to‐pay threshold below €473, between €473 and €4670, and beyond €4670 per correctly diagnosed case. At a price of €500 per Endotest®, strategy I was dominated by all other strategies. At €1000, the ICERs of strategies II and III were €724 and €387 per correctly diagnosed case, respectively, compared with strategy I. Conclusion: The present study demonstrates the value of the Endotest® from an economic perspective.